Public Policy and Water in Florida - Roy R. Carriker; Tatiana Borisova (EDIS)
FE799, an 8-page illustrated fact sheet by Roy R. Carriker and Tatiana Borisova, describes the state policies and regulations that provide the framework for water resources use and the impact of human activities on water resources in the state of Florida. Includes references. Published by the UF Department of Food and Resource Economics, May 2009.